Digitalization and enterprise architecture management: a perspective on benefits and challenges - Michael Möhring; Barbara Keller; Rainer Schmidt; Kurt Sandkuhl; Alfred Zimmermann (SN Business & Economics, 2023)
Many companies digitally transform their business models, processes, and services. They have also been using Enterprise Architecture Management approaches for a long time to synchronize corporate strategy and information technology. Such digitalization projects bring different challenges for Enterprise Architecture Management. Without understanding and addressing them, Enterprise Architecture Management projects will fail or not deliver the expected value. Since existing research has not yet addressed these challenges, they were investigated based on a qualitative expert study with leading industry experts from Europe. Furthermore, potential benefits of digitalization projects for Enterprise Architecture Management were researched. Our results provide a theoretical framework consisting of five identified challenges, triggers and a number of benefits. Furthermore, we discuss in what ways digitalization and EAM is a promising topic for future research.
Keywords: 330; Digitalization; Enterprise architecture management; Enterprise management; IT management